PROBLEMS OF QUALIFICATION AND IMPLEMENTATION OF CRIMINAL PROCEDURAL LAW STANDARTS IN MODERN LAW ENFORCEMENT PRACTICE - Kasapohlu , Svitlana (Collection of scientific papers «ΛΌГOΣ», 2025)
The effectiveness of criminal procedural law is determined not only by its legislative perfection but also by the real mechanisms of its implementation. In particular, issues of law enforcement play a crucial role, encompassing both the qualification of crimes and the procedural aspects of law enforcement agencies’ work. The lack of clear definitions and the presence of evaluative concepts in criminal procedural legislation create difficulties in judicial practice, necessitating thorough analysis and the development of effective mechanisms to overcome these challenges.